PENGEMBANGAN MEDIA EDUKASI ANTI PERUNDUNGAN ANAK DI LINGKUNGAN SEKOLAH BERBASIS KOMIK - Munthakhabah R, Cita St.; Sapriadi, Sapriadi; Iwan, Iwan (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
The purpose of this study was to determine the stages of development, validity and effectiveness of anti-bullying educational media in the school environment based on comics. This study is a Research and Development study using the 4D model, namely, (1) Define by conducting initial observations and needs analysis, (2) Design, namely designing comics and the suitability of the content, (3) Development, namely by conducting expert judgment validation, one-to-one trials, and small group trials, (4) Disseminate by implementing anti-bullying educational media for children in the school environment based on comics at SMPN 1 Wonomulyo, and the last stage is evaluation through Pre-Test and Post-Test. The limitations of this study are to determine the development of the validity and effectiveness of an educational media in one middle school in Wonomulyo Regency, namely SMPN 1 Wonomulyo with a research sample of class VII. This study produces valid and effective comic-based educational media. The valid category is reviewed from the results of the recapitulation of expert judgment validation, one-to-one trials and small group trials whose values are in the Valid criteria. The effectiveness category is reviewed from the results of the recapitulation of the evaluation analysis through the Pre Test and Post Test. Based on these data, comic-based anti-bullying educational media is valid and effective for increasing students' knowledge about the impact of bullying behavior.